Determination of the accumulation of heavy metals of river sediment by plants - Kovács-Bokor, Éva; Domokos, Endre; Kiss, Endre (International Journal of Engineering and Management Sciences, 2019)
Danube is the main river of Hungary. Danube and its floodplains and oxbow lakes are operating as ecological corridors, although their industrial, logistic and touristic role is not negligible. It is well known, that from the source to the estuary of the river Danube there are many industrial facilities. This heavy industrial pollution had effected on the water quality. The most dangerous components of the sewage water of these facilities are heavy metals, which can be found in the water as well as in the sediment. These toxic elements can cause significant health risks, because they can accumulate in the food-chain. The main aim of our research is to investigate the accumulation rate of the heavy metal content of the river sediment in the different parts of the test plants. The main sampling place of our research was a sediment dump was created by excavation from the Open Beach of Dunaújváros in 2009. During our measurements we analysed the cadmium, nickel, lead, chromium, copper and zinc concentration of the sediment and the plants. The test plants, which are growing on this sampling place, were parella (Rumex patientia), perennial rye-grass (Lolium perenne), sedge (Carex riparia), bistort (Persicaria maculosa). The extraction of the heavy metal content of the samples was made according to the MSZ Hungarian standard. The concentration of heavy metals were analysed with AAS (atom absorption spectrometer). According to our results we determined that parella could accumulate cadmium, nickel, chromium and zinc in its upper stem, on the other hand bistort could accumulate these elements mainly in its leaves. These information will be important in the case of the in-situ remediation of a polluted area in the future.